Memaknakan Pengalaman Traumatis Kekerasan:Hannah Arendt dan Viktor Frankl - Felix Lengkong (Respons: Jurnal Etika Sosial, 2009)
Holocaust is such a traumatizing event, not only to those who had a direct contact with it such as Hannah Arendt and Viktor Frankl, but also to many people who have indirectlygot to know about it through reading or watching Holocaust movies. Assuming that bothHannah Arendt and Viktor Frankl were somehow affected by such a traumatic experience, thisarticle traces out such an effect in the works and writings of those celebrated thinkers. From the perspective personality psychopathological symptoms – traced in the life history of both – itconcludes that there were no traces of posttraumatic stress in the life of both thinkers. Seeminglytheir positive cognitive processes took them from posttraumatic stress control. Instead of succumbing to despair, in line with Frankl’s theory – they found meaning in the suffering.